MAGIC detection of sub-TEV emission from gravitationally lensed blazar QSO B0218+357. Issue Volume 12:Issue S324(2016) (23rd June 2017) - Prester, D. Dominis; Sitarek, J.; Becerra, J.; Buson, S.; Lindfors, E.; Manganaro, M.; Mazin, D.; Rosillo, M. Nievas; Nilsson, K.; Stamerra, A.; Tavecchio, F.; Vovk, Ie.; et al.
Abstract : The blazar QSO B0218+357 is the first gravitationally lensed blazar detected in the very high energy (VHE, E > 100 GeV) gamma-ray spectral range (Ahnen et al. 2016). It is gravitationally lensed by the intervening galaxy B0218+357G ( z l = 0.68466 ± 0.00004, Carilli et al. 1993), which splits the blazar emission into two components, spatially indistinguishable by gamma-ray instruments, but separated by a 10-12 days delay. In July 2014 a flare from QSO B0218+357 was observed by the Fermi -LAT (Large Area Telescope, Atwood et al. 2009, Ackermann et al. 2012), and followed-up by the MAGIC (Major Atmospheric Gamma Imaging Cherenkov) telescopes, a stereoscopic system of two 17m Imaging Atmospheric Cherenkov Telescopes located on La Palma, Canary Islands (Aleksić et al. 2016a, 2016b), during the expected time of arrival of the delayed component of the emission. MAGIC could not observe the leading image due to the Full Moon. The MAGIC and Fermi -LAT observations were accompanied by optical data from KVA telescope at La Palma, and X-ray observations by Swift -XRT (Fig. 1 left). Variability in gamma-rays was of the order of one day, while no variability correlated with gamma-rays was observed at lower energies. The flux ratio of the leading to trailing image in HE gamma-rays was larger than in the flare of QSO B0218+357 observed by Fermi -LAT in 2012 (Cheung et al. 2014). Changes in the observed flux ratio can be caused by gravitational microlensing on individual stars in the host galaxy (Neronov et al. 2015), or by other compact objects like for ex. clumps in giant molecular clouds (Sitarek & Bednarek 2016).